Pilgrims' satisfaction with metro operations during Hajj - Lucas Weber; Sven Müller; Knut Haase (Public Transport, 2023)
To date, very little research has been conducted regarding visitor satisfaction with operations at mega events and mass gatherings. We examine the user satisfaction of passengers of the Makkah Metro in Saudi Arabia during Hajj. Hajj is one of the largest mass gatherings in the world. Our aim is to compare the sensitivities towards waiting time of different user groups in order to identify user groups that are particularly sensitive to waiting time. Those user groups might then be scheduled preferably to the Hajj rituals in such a way that their expected waiting time is minimized. For this reason, we are interested in the interactions between the passengers' person-specific attributes and their perceived waiting time at the stations. We apply an ordered logit model to unique survey data. Our results reveal that women are much more sensitive to waiting time than men. In addition to gender, a pilgrim's country of origin also seems to play a significant role, which has operational implications on crowd management.
Keywords: 380; Makkah Metro; Hajj; Waiting time; User satisfaction; User survey; Ordinal logit; Mega events; Crowd Operations Management